Interfacial architecture on the fractal support: polycrystalline gold films as support for self-assembling monolayers - Snopoka, B.; Strizhak, P.; Kostyukevich, E.; Serebriy, V.; Lysenko, S.; Shepeliavii, P.; Priatkin, S.L.; Kostuykevich, S.; Shirshov, Yu.; Venger, E. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
Multifractal analysis is performed for description of the surface topography of thin polycrystalline gold film. Its structure was modified by annealing at different temperatures in the range 20÷200 ⁰C and films were imaged by Atomic Force Microscopy. Image was analyzed as a collection of layers taken parallel to the mean surface. Fractal subsets with different scaling properties were described by multifractal divergence (e.g. the difference between maximal and minimal values of the f (a) spectrum). This allowed to highlight the effect of the temperature of film annealing on the surface structure. We found that fractal diversity jumps down in the temperature range 130÷140 ⁰C. Therefore, phase transition occurs in the system. Below the temperature of the phase transition the surface topography is characterized by high roughness and existence of small-scale irregularities. At critical temperature the surface structure undergoes morphological transition caused by melting of small-scale irregularities. The melting also results in a decrease of the surface roughness due to the flowing down of gold crystallites. A notable feature of the approach is its ability to highlight a possible influence of substrate structure on the adsorption/self-assembling processes at the interface, which may be disturbed by the surface irregularities. The typical and expressive example taken from the self-assembling on the polycrystalline substrate. Particularly, substrate topography determines an order of thiols layers resulting in peculiarities of chemical functionality of obtained material. It was shown that formation of well-ordered monolayers of ω-substituted alkanethiols on gold films occurs only if the freshly evaporated gold films were annealed at temperature more than ca.120 ⁰C. The analysis of surface peculiarities allows suggesting that this behavior is caused by disappearance of short-scale multifractal structures. Therefore, the multifractal analysis opens a new avenue for both characterization and direct prediction of surface properties. Particularly, it gives a hint regarding a formation of the Euclidean two-imensional structures at the multifractal substrates.